2020
DOI: 10.1186/s12913-020-05897-w
|View full text |Cite
|
Sign up to set email alerts
|

Costs and its drivers for diabetes mellitus type 2 patients in France and Germany: a systematic review of economic studies

Abstract: Background Type 2 diabetes represents an increasingly critical challenge for health policy worldwide. It absorbs massive resources from both patients and national economies to sustain direct costs of the treatment of type 2 diabetes and its complications and indirect costs related to work loss and wages. More recently, there are innovations based on remote control and personalised programs that promise a more cost-effective diabetes management while reducing diabetes-related complications. In s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 72 publications
(223 reference statements)
1
11
0
Order By: Relevance
“…Our analysis of diabetes-related costs is in accordance with the recent literature, reporting hospitalizations, AD prescriptions, higher HbA1c, and BMI, as well as treatment with insulin as major cost drivers for public healthcare expenditures in diabetes [39]. Furthermore, we identified one previous study that evaluated the direct treatment costs of T2D patients who were initiating insulin therapy (INSTIGATE [40]).…”
Section: Discussionsupporting
confidence: 72%
“…Our analysis of diabetes-related costs is in accordance with the recent literature, reporting hospitalizations, AD prescriptions, higher HbA1c, and BMI, as well as treatment with insulin as major cost drivers for public healthcare expenditures in diabetes [39]. Furthermore, we identified one previous study that evaluated the direct treatment costs of T2D patients who were initiating insulin therapy (INSTIGATE [40]).…”
Section: Discussionsupporting
confidence: 72%
“…Currently, the percentage of pregnancies affected by gestational diabetes mellitus is approximately 3-8% and the number of cases is systematically increasing [14,15]. The factors favoring the rapid development of diabetes include socio-cultural changes, aging societies, urbanization and modern lifestyles, i.e., the increased consumption of processed foods and carbohydrates, a significant reduction of the proportion of vegetables and fruit in the diet, and, finally, decreased physical activity [79][80][81][82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of diabetes and its complications is expensive for both patients (due to the cost of anti-diabetic medication) and national economies (through the indirect costs incurred through loss of work, productivity or earnings) [81]. As reported by Wierzba et al [103], in Poland spending on diabetes treatment is increasing steadily, and approximately 80% of diabetics in Poland state that they cannot afford optimal, modern diabetes therapy [104].…”
Section: Discussionmentioning
confidence: 99%
“…Health economic studies of innovative tools that aim to optimize diabetes management are crucial to enhancing their acceptance by health authorities in the long term. Furthermore, diabetes-related complications lead to substantial additional costs, as assessed in Sweden in 2016 (€1317 per patient) [14], while a systematic review in France and Germany in 2020 found that costs resulting from complications were the main cost component [15]. Diabetic retinopathy, diabetic kidney disease and diabetic foot ulcer are among the main complications studied, with annual costs of €2297, €2843-3908, and €10,604, respectively [16].…”
Section: Introductionmentioning
confidence: 99%